Biallelic variants p.Arg1133Cys and p.Arg1379Cys in COL2A1: Further delineation of phenotypic spectrum of recessive Type 2 collagenopathies. Issue 2 (22nd November 2019) - Girisha, Katta M.; Bhavani, Gandham S.; Shah, Hitesh; Moirangthem, Amita; Shukla, Anju; Kim, Ok‐Hwa; Nishimura, Gen; Mortier, Geert R.
Abstract: The phenotypic spectrum of Type 2 collagenopathies ranges from lethal achondrogenesis Type 2 to milder osteoarthritis with mild chondrodysplasia. All of them are monoallelic except for the two recent reports showing that biallelic variants in COL2A1 can cause spondyloepiphyseal dysplasia congenita in two children. Here we report two additional families with homozygous variants, c.4135C>T (p.Arg1379Cys) and c.3190C>T (p.Arg1133Cys) in COL2A1 resulting in two distinct skeletal dysplasia phenotypes of intermediate severity. Though all six patients from four families exhibit a spondylo‐epimetaphyseal dysplasia, they demonstrate a wide variation in severity of short stature and involvement of epiphyses, metaphyses, and vertebrae. We hypothesize that the variants are likely to be hypomorphic, given the underlying mechanisms of disease causation for known heterozygous variants in COL2A1 . With this report, we provide further evidence to the existence of autosomal recessive Type 2 collagenopathy.